ORIGINAL PAPER Assessment of gait parameters in rheumatoid arthritis patients after knee surgery - Prusinowska, Agnieszka; Sobol, Jacek; Małdyk, Paweł (Reumatologia/Rheumatology, 2005)
The results of the gait analysis after knee operation – synovectomy and replecement in RA patients are presented and compared in this article. Also, the effect of standard early postoperative rehabilitation on gait stereotype is discussed.